2021
DOI: 10.1186/s13071-021-05054-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and prevalence of trypanosomes in cattle distributed within the Jebba axis of the River Niger, Kwara state, Nigeria

Abstract: Background Trypanosomiasis is a fatal disease that threatens the economy of at least 37 countries in sub-Saharan Africa, particularly with regard to livestock farming. In this study, we investigated the prevalence of trypanosome infection in cattle, and molecularly identified the species of trypanosomes in infected cattle and the spatial distribution of trypanosome-infected herds along the Jebba axis of the River Niger. Methods A randomized cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The parasite Trypanosoma (megatrypanum) theileri is prevalent in cattle throughout the world with surveys indicating a presence in >80% of cattle in the US, Europe and the United Kingdom ( 21 – 25 ). In Sub-Saharan Africa, T. theileri is highly prevalent in the cattle population and coexists with AT-causing trypanosomes ( 14 , 26 , 27 ). T. theileri is transmitted by tabanid flies and is considered a commensal pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…The parasite Trypanosoma (megatrypanum) theileri is prevalent in cattle throughout the world with surveys indicating a presence in >80% of cattle in the US, Europe and the United Kingdom ( 21 – 25 ). In Sub-Saharan Africa, T. theileri is highly prevalent in the cattle population and coexists with AT-causing trypanosomes ( 14 , 26 , 27 ). T. theileri is transmitted by tabanid flies and is considered a commensal pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Five of these reported infection in cattle - bovine trypanosomiasis. 27,28, 29, 30,31 Two studies investigated trypanosomiasis infection in pigs – porcine trypanosomiasis. 32, 33 Three studies investigated infection in ruminants – sheep, goat, cattle, 34,35,36 while one study investigated in dogs – canine trypanosomiasis.…”
Section: Resultsmentioning
confidence: 99%
“…Even with the renewed efforts by the scientific communities to control AAT, the disease has continued to pose a great constraint to livestock production in sub-Saharan Africa ( Meyer et al, 2016 ; Habeeb et al, 2021 ) mainly because the available trypanocides are faced with major drawbacks ( Assefa and Shibeshi, 2018 ). In light of this, the present study demonstrated the therapeutic benefits of β-sitosterol on T. congolense proliferation, anemia amelioration, kidney damage, and the TconTS1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases not only affect human or animal health but also affect the economic well-being of the continent ( Sun and Amon, 2018 ). One of the most important tropical diseases is African Animal Trypanosomiasis (AAT) caused by parasitic protozoan species including Trypanosoma congolense (T. congolense) , Trypanosoma vivax (T. vivax) , and Trypanosoma brucei brucei (T. brucei brucei) that are spread across the 37 sub-Saharan African countries where they affect livestock production ( Habeeb et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%